FOOD RESISTANCE: Investigating modes of production of subjetivity through eating practices in the contemporary city - Craveiro, Camila Caires (Geografares, 2018)
The article begins with a discussion of the field of studies of Subjectivity (GUATTARI, ROLNIK, 2010), to reflect on subjective modes of production, through eating practices in the context of the contemporary city. It aims to explore the transformations that have occurred in the last century in the context of cities and their consequences in the logic of the production of food practices. Such reflection will be woven based on the cartographic method (PASSOS, KASTRUP, ESCÓSSIA, 2014ª, 2014b, FONSECA, NASCIMENTO MARASCHIN, 2012), supporting the cartography of the multiplicity of discourses and food practices present in the context of the contemporary city. The article is based on a bibliographical review involving discussions of the human and social sciences that can expand the field of discussion, presenting already, the perspective that this field does not fit within specific disciplinary sectors. As a result of the analyzes, it is possible to show that the growing urbanization phenomenon in connection with the modernization / mechanization of agricultural practices - supported by capitalist development - produces food practices as a reflection and reproduction of this mode of development. Resulting in the constitution of the habit of eating as a mere act of consumption, one among so many products on the shelves of the market. At the same time, it is possible to see the act of eating as a possibility of reinventing the ways of life in this current context, making bets in an eclogical (GUATTARI, 1990; SANTOS, 2002), as a reinvention of the practices of self care and (Foucault, 2006b). Keywords: subjectivity; city; food practices.